Case Report: IGFBP5-ALK fusion-positive case of high-grade endometrial stromal sarcoma with response to ALK-targeted therapy - Zhang, Weiwei; Wu, Jinkun; Song, Shujie; Cheng, Yu (Frontiers in Oncology, 2026)
BackgroundHigh-grade endometrial stromal sarcoma (HG-ESS) is a very rare and aggressive uterine malignancy. Although recurrent genetic alterations such as YWHAE-NUTM2 fusions and BCOR alterations are well recognized, ALK rearrangements have not been previously reported in HG-ESS, and the efficacy of ALK inhibitors in this context remains unknown.Case descriptionA 51-year-old woman presented with irregular vaginal bleeding and underwent a total abdominal hysterectomy with bilateral salpingo-oophorectomy (TLH/BSO) and omentectomy. Histopathological and immunohistochemical analyses following hysterectomy confirmed HG-ESS. Postoperative imaging revealed rapid disease progression with pulmonary and pelvic metastases. After failure of gemcitabine/docetaxel chemotherapy, next-generation sequencing identified an IGFBP5-ALK fusion (breakpoint: IGFBP5 exon 1 – ALK exon 19), a TERT promoter mutation, and a homozygous CDKN2A/CDKN2B/MTAP deletion. The patient received iruplinalkib, a second-generation ALK inhibitor, and achieved a partial response within six weeks, with a >47.2% reduction in target lesions. The patient remains on therapy to date and treatment was well-tolerated.ConclusionThis case highlights the first documented response to an ALK inhibitor in ALK-rearranged HG-ESS. The findings underscore the importance of comprehensive molecular profiling in identifying targetable alterations in rare sarcomas and support the use of iruplinalkib as an effective therapeutic option in this setting.